Analysis of The Development of Online Business in Indonesia and Recommendation for Online Startup Entrepreneurs - Wafiah, Zahratul; Titus, Amol (The Indonesian Journal of Business Administration, 2014)
Abstract - E-commerce is an exchange of goods or money by buying and selling goods via internet which includes the movement of goods from one place to another. Online shopping is a form of e-commerce. This business directly connects sellers with buyers (Business-to-Consumer, B2C) via the Internet. In Indonesia, the online shopping retail product is currently experiencing high growth. Unfortunately despite high growth, its share is still small compared with total retail sales. There are still a lot of rooms that could make online shopping is growing and supporting the Indonesian economy. These rooms can be filled by companies/entrepreneurs who are interested in opening a business through the internet. The experience of some business owners can be studied and used as an example for the startup entrepreneurs. Products that are interested more to the Indonesian market can be known by survey. Those can be reference for the startup entrepreneurs. Online shop is very attractive and offers plenty of opportunities to new and young entrepreneurs as well as SMEs. Even though the potential barriers are there however these potential barriers can be eliminated. It is evident from this thesis that Indonesian consumers who are very tech savvy are using internet to purchase items. E-commerce is helping company reach remote areas and link-up with other traditional industries. The potential size of market is huge and will grow as internet infrastructure and connectivity improves. Indonesia has potential to become one of the largest e-commerce nations with many benefit for industry and consumers.Â Keywords: e-commerce, online shopping, Business-to-Consumer